Motorola becomes a disk jockey [cellphone music]. - Ross, P.E.
This paper describes Motorola's new music downloading service, called iRadio, a total music system for the car, the street, and the home. Designed to encourage impulse purchases, iRadio allows its subscribers access to the massive musical collections of major music labels. However, Motorola will do well to provide a few value-added features to this subscription-based service if it wants to compete with conventional and satellite radios as well as existing Internet music sites.
Keywords: Internet music sites; Motorola; Cellphone music service; Conventional radios; Digital music; iRadio; Satellite radios